Pengelolaan Sampah Plastik Rumah Tangga Dengan Metode Ecobrick Di Gaten Sumberrejo Tempel Sleman - Sasti Alifia Widya Saputri; Khoerul Yusri Argian; Saniya Afdalriva Mizandya; Tiyo Sandhita; Nisa Indriyani Putri; M.Mirza Fauzie; Sardjito Eko Windarso (JPS : Jurnal Pengabdian Serulingmas, 2022)
Indonesia's health development is in the phase of re-emerging diseases. One such case is Dengue Hemorrhagic Garbage is the rest of human activities that are not used, not liked and will be discarded. Based on its compounds, waste can be classified into 2 (two) namely Organic Waste and Inorganic Waste. Simply put, people generally process plastic by burning. This method is done because it is relatively easy and the volume of garbage after burning is significantly reduced even by 90%. Plastics exposed to high temperatures (burned or exposed to sunlight) will secrete toxic particles carried by rain. These particles then contaminate the water, air, and soil around us. This causes the quality of our environment to be poor. So far we only know plastic management in 3 ways: reuse, reduce, recycle. Seeing the problem of plastic waste that is not well managed and the lack of knowledge of citizens about plastic waste management with ecobrick methods, students of the Community PKL Department of Environmental Health located in Gaten Hamlet agreed to hold community service activities through extension themed Zero Waste: Plastic Waste Management into Ecobrick. This activity is able to increase the awareness and understanding of trainees about plastic waste management. The creation of a relatively easy and simple ecobrick is one of the factors that make the enthusiasm of residents increase to apply it starting from their homes. Efforts to manage waste with ecobricks methods are expected to be one of the solutions to reduce plastic waste so as to reduce plastic pollution in the surrounding environment.